FRI0227 Acpa fine specificity is associated with increased plasmablast numbers and worse clinical response to rituximab in rheumatoid arthritis. (23rd January 2014) - Vital, E. M.; Israelsson, L.; Nogueira, L.; Malmström, V.; El-Sherbiny, Y.; Rawstron, A.; Serre, G.; Klareskog, L.; Ponchel, F.; Emery, P.
Abstract : Background: Quality and duration of response to rituximab in seropositive RA is variable. Higher pre-and post-treatment plasmablasts are associated with non-response and early relapse, but have not previously been linked to RA-specific antibodies. To date ACPA fine specificity has not been investigated in B cell depletion therapy. Objectives: To assess the relationship between ACPA fine specificity, clinical response and B cell subsets in RA patients treated with rituximab. Methods: 82 patients with active RA were treated with 2x1000 mg rituximab. Clinical response was assessed using DAS28 and EULAR criteria at 0, 6 and 12 months. Presence of antibodies was analysed by ELISA as previously described. The 98 th percentile cut-off was used for positivity. A positive and a negative control serum and a standard of pooled antibody-positive sera were included on each plate. We measured at 0 and 6 months IgM-, IgG- and IgA-RF; anti-collagen II antibodies (CII-C1, CII-U1); anti-CCP2 and other antibodies against citrullinated targets: Fibrinogen (AhFibA) and the peptides Vimentin60-75(Vim60-75), CEP-1 from alpha-enolase, a collagen II peptide (CIICitC1), and peptides from the Fibrinogen alpha and beta chains (Fib alpha36-50, Fib beta36-52, Fib beta60-74). Results: Mean (SD) baseline DAS28 was 5.63 (1.08). Presence of each RF isotype was associated with higher DAS28, but presence of individual ACPA specificities was not associated with baseline disease activity. EULAR Non/Moderate/Good responses at 6 months were 26/38/37%, respectively. Clinical response was not related to IgM/G/A-RF status at baseline or change in titre. CCP2 was not associated with any clinical outcome. EULAR Non-responders had higher baseline titres of antibodies to CIICitC1 (p=0.038), CEP-1 (p=0.088) and Fib beta60-74 (p=0.093). There was a trend to lower Mod/Good response rate for patients positive for each ACPA specifity but this was significant only for Vim60-75 (61 vs. 84%, p=0.031). However, the total number of ACPA fine specificities at baseline was significantly higher in patients with EULAR Non response (median (IQR): 4(2-5) vs. 2(1-4), p=0.008). Patients with EULAR response at 6 months who maintained response to 12 months had significantly lower post-treatment titres of IgM-RF and Vim60-75, a trend to lower Fib beta 60-74 but no difference in CCP2. After a second cycle of rituximab, there was a further reduction in AhFibA (p=0.046), Vim60-75 (p=0.043) and CEP-1 (p=0.068), but not CCP2 (p=0.382). Number of ACPA fine specificities was associated with higher numbers of plasmablasts in early B cell repopulation at 6 months (p<0.001). Conclusions: These results show that efficacy of B cell depletion in RA is linked to ACPA fine specificity, and that early plasmablast repopulation is disease-associated. Disclosure of Interest : None Declared